The Effect of Demographic Variables on Secondary Level Students' Attitude towards Mathematics in Nepal - Kunwar, Rajendra (Researcher: A Research Journal of Culture and Society, 2020)
Student's attitude towards mathematics is a global issue that directly influences the students' achievement in mathematics. The study aimed at investigating the students' attitudes towards mathematics and the effects of demographic variables on their attitude in the selected grade IX Students in Provence No 1, Nepal. The study has adopted a quantitative survey design. A total of 540 grade IX students were selected randomly and the revised attitude scale ATMI of Tapia and Marsh (2004) was adopted to find out their attitudes towards mathematics and the effect of demographic variables. The data were analyzed using mean, standard deviation, and multiple linear regressions. The results of the study showed that the students' attitude towards mathematics is positive. Similarly, the effects of students' attitudes towards mathematics in terms of demographic variables (age, gender, family type, parent's education, parent's occupation, school location, and ecological region) were found low. The attitude of the students at a different age level showed a greater decline in attitudes as the students increase their grade level. However, the results showed that other considerable variables may have more impact on students' attitudes towards mathematics.